Health surveillance of populations exposed to pesticides: scope review (Research, Society and Development, 2021)
Brazil is one of the countries that most consumes pesticides in the world and the number of studies that identify and monitor health actions aimed at chronically exposed populations is still incipient. Thus, the objective was to identify health surveillance actions oriented to populations exposed to agrochemicals implemented in Brazil. A Scope Review was performed in the Web of Science (WOS), Scopus, Brazilian Virtual Health Library (BVS) ), Scielo, Cochrane and Pub Med databases. The descriptors "Public Health Surveillance", "Agrochemicals" and "Surveillance of the Workers Health" were used. Eleven articles were part of this review, it was possible to identify health surveillance actions for populations exposed to agrochemicals in nine articles, two did not identify any action in the scope evaluated. Among the main actions identified are the notification of pesticide poisoning, support for diagnosis and treatment of poisoning, use of information systems for information management, technical training of health professionals, monitoring of water and food contamination, and preparation of State Action Plans for Surveillance of Populations Exposed to Agrochemicals. The literature indicates that implementing health surveillance practices for this public involves intersectorial and interdisciplinary processes that incorporate the productive process of agribusiness into local situational analyses.